Compensated electron and hole pockets in an underdoped high-T-c superconductor - Sebastian, SE; Harrison, N; Goddard, P; Altarawneh, M; Mielke, C; Liang, R; Bonn, D; Hardy, W; Andersen, O; Lonzarich, G (2010)
We report quantum oscillations in the underdoped high-temperature superconductor YBa2 Cu3 O6+x over a wide range in magnetic field 28≤ μ0 H≤85 T corresponding to ≈12 oscillations, enabling the Fermi surface topology to be mapped to high resolution. As earlier reported by Sebastian [Nature (London) 454, 200 (2008)10.1038/nature07095], we find a Fermi surface comprising multiple pockets, as revealed by the additional distinct quantum oscillation frequencies and harmonics reported in this work. We find the originally reported broad low-frequency Fourier peak at ≈535 T to be clearly resolved into three separate peaks at ≈460, ≈532, and ≈602 T, in reasonable agreement with the reported frequencies of Audouard [Phys. Rev. Lett. 103, 157003 (2009)10.1103/PhysRevLett.103.157003]. However, our increased resolution and angle-resolved measurements identify these frequencies to originate from two similarly sized pockets with greatly contrasting degrees of interlayer corrugation. The spectrally dominant frequency originates from a pocket (denoted α) that is almost ideally two-dimensional in form (exhibiting negligible interlayer corrugation). In contrast, the newly resolved weaker adjacent spectral features originate from a deeply corrugated pocket (denoted γ). On comparison with band structure, the d -wave symmetry of the interlayer dispersion locates the minimally corrugated α pocket at the "nodal" point knodal = (π/2,π/2), and the significantly corrugated γ pocket at the "antinodal" point kantinodal = (π,0) within the Brillouin zone. The differently corrugated pockets at different locations indicate creation by translational symmetry breaking-a spin-density wave has been suggested from the suppression of Zeeman splitting for the spectrally dominant pocket. In a broken-translational symmetry scenario, symmetry points to the nodal (α) pocket corresponding to holes, with the weaker antinodal (γ) pocket corresponding to electrons-likely responsible for the negative Hall coefficient reported by LeBoeuf [Nature (London) 450, 533 (2007)10.1038/nature06332]. Given the similarity in α and γ pocket volumes, their opposite carrier type and the previous report of a diverging effective mass in Sebastian [Proc. Nat. Am. Soc. 107, 6175 (2010)10.1073/pnas.0913711107], we discuss the possibility of a secondary Fermi surface instability at low dopings of the excitonic insulator type, associated with the metal-insulator quantum critical point. Its potential involvement in the enhancement of superconducting transition temperatures is also discussed. © 2010 The American Physical Society.